Mitopoéticas do amor: a representação dos amantes em “U Amassu e U Dubradú’’, de Patrícia Bastos - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
This study analyzes the song “U amassu i u dubradú,” by Patrícia Bastos, as an aesthetic and political statement of Amapá's identity. It aims to explore the creation of a mythopoetics of love that transforms the Amazonian lived experience into language. The theoretical framework relates fiction as a necessity (Sperber; Ricoeur) and semiotic conversion (Paes Loureiro), establishing a dialogue with the structures of the imaginary (Durand) and material imagination (Bachelard). From the counter-colonial perspective of Nêgo Bispo and Luiz Rufino, the analysis of the four lovers highlights the rejection of exploitative logic in favor of biointeraction. The work establishes an “enchanted science,” in which loving the Amazon is an act inseparable from belonging and protecting the territory.
Keywords: Música Brasileira; Identidade Cultural; Cultura Amazônica; Patrimônio Cultural Imaterial; CNPQ::LINGUISTICA, LETRAS E ARTES::LETRAS; ODS 10 – Redução das desigualdades; ODS 11 – Cidades e comunidades sustentáveis; ODS 12 – Consumo e produção responsáveis; ODS 13 – Ação contra a mudança global do clima